CONFLICT MODEL ON WORK MOTIVATION - Agustina, Granit; Febrian, Feby (Dinasti Publisher, 2021)
Each agency must be able to manage employees by applying appropriate conflict models according to organizational needs that can increase a person's work motivation for a job. This study aims to determine whether the functional and functional effects on employee work motivation. This research is a descriptive and verification research using path analysis, where the population of respondents is all employees of the tourism and culture office of West Java province as many as 200 people with a sample of 67 respondents using SPSS 24 software. From the results of the respondents' responses that have been distributed So simultaneously the test results show that the conflict model affects work motivation with a functional effect of 0.493 and a significant effect on dysfunctional 0.198 and simultaneously the effect of the two variables on work motivation is 0.295. From the research results partially know that functional is more dominant in influencing work motivation than dysfunctional in the conflict model.